O serviço de acolhimento de crianças junto ao abrigo “Casa Mamãe Margarida”: Processo de (des)construção de identidade impostas. - Gomes, Elias Bandeira (2019)
ABSTRACT Raising the discussion about how objectification practices occur in subjectivation processes of subjects, the research questions whether it is possible that subjectivities and identities imposed on victims of abuse can be re-signified when they are in environments where they can develop healthy relationships, similarly to the ones in question. shelter institutions. To work on this problem, Casa Mamãe Margarida was chosen, an institution dedicated to the care of children and adolescents who are at risk and social vulnerability. As a practice of approximation and data collection, the ethnographic model was used, assuming as the guiding theoretical framework the conceptual framework of the Sociology of Childhood. Given the references chosen, considering the importance of individual recognition as a person and the right to high determination of their own existence, the research sought to observe children always as subjects with the ability to elaborate their own. From this perspective each speech, gesture, agreement or denial was strictly observed. Recognizing the value of contexts in the constitution of subjects as social and historical agents. As such, the research understands that they are subject to be affected by the dynamics established in the social treatments in which the exchange relation is imposed, providing both the subjects and the environment, permanent interactions from which mutual influences derive (BOURDIEU, 2003). In this reading, subjects and means are no longer considered neutral agents, to be understood in the light of relational dynamics, in which the constant construction of the person prevails (GHADIRI, DAVEL, 2006). Given this assumption and before the “collection” concluded, the research understands that, even when subjected to practices of oppression, each person has the possibility of resignifying experiences, giving new meanings to existence, when offered the environment of support and respect. the person. Keywords: Childhood, Identity, Child Abuse, Oppression Practices, Subjectivity of Subjects.